Acetylcholine and cholinergic receptors. (March 2019) - Brown, David A.
This review provides a distillate of the advances in knowledge about the neurotransmitter functions of acetylcholine over the 50-year period between 1967 and 2017, together with incremental information about the cognate nicotinic and muscarinic acetylcholine receptors, and some brief comments on possible advances in the near future. The text is supplemented by a timelines figure indicating the dates of some key advances in knowledge about acetylcholine receptors and a box-figure providing a snapshot of selected papers about acetylcholine published in the year 1967.